Suggerimenti di lettura - Lazzarini, Carmine; Macario, Giorgio; Scanarotti, Roberto; Macario, Giorgio; De Toni, Ivana; Sperindio, Loriana; Giusti, Mariangela (Autobiografie. Ricerche, pratiche, esperienze, 2024)